Increase in cytosolic Ca2+ produced by hypoxia and other depolarizing stimuli activates a non-selective cation channel in chemoreceptor cells of rat carotid body - Kang, Dawon; Wang, Jiaju; Hogan, James O.; Vennekens, Rudi; Freichel, Marc; White, Carl; Kim, Donghee (The journal of physiology, 2014)
Key points Hypoxia is thought to depolarize glomus cells by inhibiting the outward K+ current, which sets in motion a cascade of ionic events that lead to transmitter secretion, increased afferent carotid sinus nerve activity and increased ventilation. Our study of Na+-permeable channels in glomus cells has revealed that hypoxia not only inhibits TASK background K+ channels but also indirectly activates a non-selective cation channel with a single channel conductance of 20 pS. Under physiological conditions, the reversal potential of the cation channel is ∼ -28 mV, indicating that Na+ influx is also involved in hypoxia-induced excitation of glomus cells. Activation of the 20 pS cation channel is present when the O2 content is 5% or less, indicating that Na+ influx occurs during moderate to severe hypoxia (<5% O2), but not mild hypoxia (>5% O2). The 20 pS cation channel is directly activated by a rise in intracellular Ca2+. Thus, factors that elevate intracellular Ca2+ such as hypoxia, extracellular acidosis and high external KCl all activate the cation channel. A feed-forward mechanism may be present in which an initial depolarization-induced rise in intracellular Ca2+ opens the Na+-permeable cation channel, and the Na+ influx causes additional depolarization and influx of Ca2+ into glomus cells. Abstract The current model of O2 sensing by carotid body chemoreceptor (glomus) cells is that hypoxia inhibits the outward K+ current and causes cell depolarization, Ca2+ influx via voltage-dependent Ca2+ channels and a rise in intracellular [Ca2+] ([Ca2+]i). Here we show that hypoxia (<5% O2), in addition to inhibiting the two-pore domain K+ channels TASK-1/3 (TASK), indirectly activates an ∼20 pS channel in isolated glomus cells. The 20 pS channel was permeable to K+, Na+ and Cs+ but not to Cl− or Ca2+. The 20 pS channel was not sensitive to voltage. Inhibition of TASK by external acid, depolarization of glomus cells with high external KCl (20 mm) or opening of the Ca2+ channel with FPL64176 activated the 20 pS channel when 1 mm Ca2+ was present in the external solution. Ca2+ (10 μm) applied to the cytosolic side of inside-out patches activated the 20 pS channel. The threshold [Ca2+]i for activation of the 20 pS channel in cell-attached patches was ∼200 nm. The reversal potential of the 20 pS channel was estimated to be −28 mV. Our results reveal a sequential mechanism in which hypoxia (<5% O2) first inhibits the K+ conductance and then activates a Na+-permeable, non-selective cation channel via depolarization-induced rise in [Ca2+]i. Our results suggest that inhibition of K+ efflux and stimulation of Na+ influx both contribute to the depolarization of glomus cells during moderate to severe hypoxia.
Im Titel ist "2+" nach Ca hochgestellt
Gesehen am 14.09.2020